Hypertension Prevention Education Through Training in Making Herbal Teas in Talango Village, Talango District, Sumenep Regency - Maharani Pertiwi K; Bastiana Bastiana; Asma Rubiah Rosyadahan; Suprapto Maat; Isdiantoni Isdiantoni; Endry Nugroho Prasetyo (UNUSA Press, 2022)
Talango Village is one of the villages located in Talango District, Sumenep Regency. The people of this village make a living mainly as fishermen and farmers. One of the habits carried out by fishers and farmers in between their activities is smoking. The nicotine in cigarette smoke can increase blood pressure and heart rate, narrow arteries, harden their walls, and make blood more likely to clot. This condition can increase the risk of hypertension or high blood pressure. Based on interviews and surveys with partners Yayasan Jala Tani Pertiwi, education about hypertension prevention needs to be carried out to prevent hypertension in fishers and hypertension in Talango Village. This problem has prompted a service team to design educational activities to prevent hypertension by manufacturing herbal teas. This activity is structured through the first step, namely the preparation stage (compilation of training modules, participant selection, and evaluation media creation), the second stage (the process of implementing activities with pre-/post-test and discussion), and the third stage (evaluating the results of the training). A total of 20 farmers and fishers who are members of the Jala Tani Pertiwi Foundation were given education about hypertension, then continued with training to make anti-hypertensive herbal teas. The evaluation results showed an increase in participants' understanding of the material provided by 34%. Participants are known to have been able to understand and make herbal teas made from Moringa leaves, jasmine flowers, lemongrass leaves, and roselle flowers. Furthermore, to increase the participants' interest in this activity, the service team also taught them how to make tea packaging and how to sell it.